Velocities of the Amery Ice Shelf's primary tributary glaciers, 2004–12. Issue 5 (28th May 2015) - Pittard, M.L.; Roberts, J.L.; Watson, C.S.; Galton-Fenzi, B.K.; Warner, R.C.; Coleman, R.
Abstract: Monitoring the rate of ice flow into ice shelves is vital to understanding how, where and when mass changes occur in Antarctica. Previous observations of ice surface velocity indicate that the Amery Ice Shelf and tributary glaciers have been relatively stable over the period 1968 to 1999. This study measured the displacement of features on the ice surface over a sequence of Landsat 7 images separated by approximately one year and spanning 2004 to 2012 using the surface feature tracking software IMCORR. The focus is on the region surrounding the southern grounding zone of the Amery Ice Shelf and its primary tributary glaciers: the Fisher, Lambert and Mellor glaciers. No significant changes in surface velocity were observed over this period. Accordingly, the velocity fields from each image pair between 2004 and 2012 were used to synthesize an average velocity dataset of the Amery Ice Shelf region and to compare it to previously published velocity datasets and in situ global positioning system velocity observations. No significant change in ice surface velocities was found between 2004 and 2012 in the Amery Ice Shelf region, which suggests that it continues to remain stable.